Design and comparative analysis of conventional and metamaterial‐based textile antennas for wearable applications. (29th January 2019) - Ali, Usman; Ullah, Sadiq; Shafi, Muhammad; Shah, Syed A.A.; Shah, Izaz A.; Flint, James A.
Abstract: In this paper, four different models of a 2.4 GHz flexible microstrip patch wearable antenna are designed and analyzed. The basic geometry of the radiating element of the antennas is a rectangular patch and is backed by conventional, mushroom‐type, slotted, and spiral electromagnetic band gap (EBG) ground planes. A 3‐mm‐thick wash cotton textile is used as a substrate material in the design of the antennas as well as EBG surfaces. An electro‐textile (Zelt) is used as a conductive material for the proposed antennas. The performance of these antennas is analyzed in terms of return loss, gain, bandwidth efficiency, and specific absorption rate (SAR) using Computer Simulation Technology Microwave Studio (CST MWS). The designed antennas are further investigated for on and off body conditions under normal and bent states. The experimental results show that the antennas radiate with an adequate gain (5.72‐7.3 dB), bandwidth (65.43‐103.1 MHz), and efficiency (55.51%‐74.04%), depending on the type of the ground plane used. The antenna backed by the mushroom‐type EBG gives the smallest value of SAR (1.79 W/kg < 2 W/kg), which makes it a suitable candidate for body worn applications in the unlicensed industrial, scientific, and medical (ISM) band.